Effect of Cytochalasin B and D on Groups of Insulin Receptors and on Insulin Action in Rat Adipocytes: POSSIBLE EVIDENCE FOR A STRUCTURAL RELATIONSHIP OF THE INSULIN RECEPTOR TO THE GLUCOSE TRANSPORT SYSTEM - Jarett, Leonard (1979)
The possible physiological importance of the groups of insulin receptors on rat adipocytes and the relationship of these groups to insulin action were investigated. The effect of cytochalasin B and D on biological actions of insulin was measured and compared with the effect of these agents on the ultrastructural distribution of groups of insulin receptors. Cytochalasin B had no effect on epinephrine-stimulated lipolysis, insulin inhibition of epinephrine-stimulated lipolysis, or insulin stimulation of protein synthesis. Cytochalasin B, over a concentration range of 50 nM to 5 μM, progressively inhibited the basal glucose transport system, as measured by glucose oxidation, 2-deoxyglucose transport, and 3-O-methylglucose transport. Insulin was capable of fully stimulating remaining basal transport at submaximal concentrations of cytochalasin B. Insulin pretreatment of adipocytes partially protected the glucose transport system from inhibition by cytochalasin B. Cytochalasin B markedly altered the distribution pattern of insulin receptors, which caused an increase in the number of single receptor molecules by decreasing the number of larger groups. A significant correlation (r = 0.964; P < 0.001) was found between the percent increase in single receptors and the percent decrease in glucose transport. Ferritin-insulin pretreatment of adipocytes prevented disruption of the groups of insulin receptors by cytochalasin B. Cytochalasin D had no effect on the biological actions of insulin or on the groups of insulin receptors. These data suggest that the ability of insulin to affect adipocyte metabolism is independent of the hormone occupying adjacent, grouped receptor sites. The marked contrast in effects of cytochalasin B and D on groups of insulin receptors and glucose transport suggests that the microfilament system is not involved in insulin action or in holding the groups of insulin receptors together, as both agents are known disrupters of microfilaments and inhibitors of actin gelation. The correlation between the effects of cytochalasin B on insulin receptor distribution and glucose transport leads to the speculation that the glycoprotein molecules containing the insulin receptor are functionally linked with the glucose transport system.